HISTORY OF BRAZILIAN EDUCATION: CURRICULUM, PEDAGOGICAL PRACTICES, AND TEACHER–STUDENT RELATIONS IN DISPUTE - Paixão e Vasconcelos, Francisco Ullissis; da Costa, Cleane Salvador; Pinto, Elisangela de Castro; Fontenele, Gizele Teles Lima; Angelim, Maria de Lourdes Pereira; Teles, Maria Elizângela Araújo; Lopes, Maria de Fátima Fernandes; Fernandes, Nazareth Ramos; Nascimento, Roberta Alves (Seven Editora, 2026)
This study presents a historical overview of Brazilian education, analyzing the constitution and transformation of pedagogical paradigms from the colonial period to contemporary configurations, which are still largely marked by the persistence of a traditional perspective and neotechnicism. The main objective of this work was to understand how different conceptions of the human being, within specific historical contexts, have influenced the organization of the curriculum, pedagogical practices, and teacher–student relationships. Grounded in authors such as Dermeval Saviani, Paulo Freire, Abraham Maslow, Carl Rogers, Henri Wallon, and Philippe Ariès, the study examines Brazilian education as a field historically shaped by disputes between different educational projects and conceptions of the subject. Throughout this trajectory, it becomes evident that educational practices have been permeated by tensions between discipline, technical training, humanization, and emancipation, directly impacting the configuration of pedagogical relationships. There is a predominance of Cartesian rationality, and the dimension of affectivity and emotion, although present at different moments, has not been established in a continuous or structuring way, being at times relegated in favor of models centered on order and technical rationality, and at others revisited as a relevant element for integral education.